Microcavity Effect in InAs/GaAs Quantum Dot Infrared Photodetector on a Si Substrate Fabricated With Metal Wafer Bonding and Epitaxial Lift-Off Techniques - Kim, Ho Sung; Ryu, G. H.; Ahn, S. Y.; Ryu, H. Y.; Choi, W. J. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
In this paper, the microcavity effect in quantum dot infrared photodetectors (QDIPs) on a Si substrate, fabricated by means of metal wafer bonding (MWB) and epitaxial lift-off (ELO) processes, was demonstrated by comparing the photocurrent spectrum and the simulated absorption spectrum. Four QDIPs having a different cavity length of 1.7, 2.8, 3, and 3.4 mu m were fabricated and compared with simulation based on the finite-difference time-domain method. The resonance peaks were observed in both photocurrent spectrum and absorption spectrum due to the microcavity formed by the bottom mirror of Pt/Au layer and the flat GaAs/air interface. The peak wavelength of the photocurrent spectrum in all four QDIPs on Si samples shows a good agreement with the simulated absorption spectrum. The bias-dependent photocurrent was also measured to study the microcavity effects more in depth. The ratio of the increased photocurrent under bias condition shows higher value in the microcavity QDIPs, showing that the microcavity contributes to generate photocurrent effectively. From these results, we believe that the MWB and ELO could be useful to make the microcavity in many integrated chemical and biosensing application.
Keywords: ABSORPTION; DESIGN